The influence of knowledge and religiosity on saving interest in Islamic banks among Ponorogo residents - Pratopo, Gentur; Hasan, Irmayanti (Universitas Islam Indonesia, 2024)
IntroductionPonorogo is a region in East Java Province, located 200 km southwest of Surabaya bordering Central Java. With a population of 973,269, Ponorogo is predominantly Muslim and known for its numerous Islamic boarding schools. This study examines the influence of knowledge and religiosity on interest in saving in Islamic banks among Ponorogo residents.ObjectivesThe objective of this research is to determine the effect of knowledge and religiosity on the interest in saving at Islamic banks among the people of Ponorogo.MethodThe study employed a quantitative method with a descriptive approach, using primary data obtained through questionnaires distributed to 400 respondents. Statistical analyses were performed to evaluate the data.ResultsThe findings show that both knowledge and religiosity significantly influence interest in saving at Islamic banks, both partially and simultaneously, at a significance level of less than 0.05. The high level of knowledge and religiosity among respondents positively affects their interest in saving in Islamic banks.ImplicationsThese results highlight the importance of enhancing financial literacy and religious awareness to boost the use of Islamic banking services. This study suggests that Islamic banks should focus on educational campaigns to increase public knowledge and leverage religious values to attract more customers.Originality/NoveltyThis study provides insights into the combined effect of knowledge and religiosity on saving behavior, particularly in a region with a strong Islamic cultural background. This study contributes to the understanding of the factors influencing the adoption of Islamic banking services.